FACTORS INFLUENCING UPTAKE OF SKILLED DELIVERY SERVICES AMONG WOMEN OF CHILD BEARING AGE AT KASANJE SUB COUNTY, WAKISO DISTRICT - NACHAP, VICKY; NAMUBIRU , REBECCA; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2025)
Background The uptake of skilled delivery services was associated with improved maternal and neonatal health outcomes. So, this study aimed to assess factors affecting the uptake of skilled delivery services among women of childbearing age in Kasanje Sub County, Wakiso district. Methodology A cross-sectional study design was used employing both quantitative and qualitative approaches to data collection using a semi-structured questionnaire. The information was manually tallied and scientific measures were used to analyze the recorded information. Thereafter, Microsoft Word and Excel programs were employed followed by a presentation in the form of frequency tables, graphs, and figures like pie charts and bar graphs. Results The results of the study were all females, in the age range of 15 to 49 years. The majority (75%) were married, (60%) had more than three children, 64% were housewives 37% travelled over 10 to reach the health centre and (66%) earned 10,000-50,000/= a month. Most (50%) used a boda boda to reach the health center and over 62% of them had to wait for over an hour before being worked on while 50% complained that midwives were rude to them. Conclusion Findings showed that the low uptake of skilled delivery services among women of childbearing age at Kasanje Sub County is highly influenced by parity, education level, occupation, social support like partner involvement, economic status, the distance needed to be moved, and the character of midwives. Recommendation Midwives and doctors in charge of maternal health need to equip themselves with good customer care service skills to positively influence and change pregnant mothers’ attitudes towards health professionals and service delivery.